2014
DOI: 10.1002/smj.2247
|View full text |Cite
|
Sign up to set email alerts
|

Managerial cognitive capabilities and the microfoundations of dynamic capabilities

Abstract: The microfoundations of dynamic capabilities have assumed greater importance in the search for factors that facilitate strategic change. Here, we focus on microfoundations at the level of the individual manager. We introduce the concept of "managerial cognitive capability," which highlights the fact that capabilities involve the capacity to perform not only physical but also mental activities. We identify specific types of cognitive capabilities that are likely to underpin dynamic managerial capabilities for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
1,368
2
61

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,266 publications
(1,481 citation statements)
references
References 131 publications
(149 reference statements)
50
1,368
2
61
Order By: Relevance
“…First, as the indirect effect of technological capabilities in our model is small in effect size, it is reasonable to expect that there might be other first-order capabilities that mediate the potential positive contribution of broad external technology access. For instance, another source of indirect effect might be a function of dynamic managerial capabilities, which are defined as the capabilities with which managers build, integrate, and reconfigure organizational resources and competences (Adner & Helfat, 2003;Helfat & Martin, 2015;Helfat & Peteraf, 2015). Firms that seek broad external technological resources probably also need strong capabilities of top managers to unleash the potential of external technological resources.…”
Section: Discussionmentioning
confidence: 99%
“…First, as the indirect effect of technological capabilities in our model is small in effect size, it is reasonable to expect that there might be other first-order capabilities that mediate the potential positive contribution of broad external technology access. For instance, another source of indirect effect might be a function of dynamic managerial capabilities, which are defined as the capabilities with which managers build, integrate, and reconfigure organizational resources and competences (Adner & Helfat, 2003;Helfat & Martin, 2015;Helfat & Peteraf, 2015). Firms that seek broad external technological resources probably also need strong capabilities of top managers to unleash the potential of external technological resources.…”
Section: Discussionmentioning
confidence: 99%
“…Many scholars (Leavy, 1998;Zollo and Winter, 2002;Helfat and Peteraf, 2015) concluded that superior performance is driven by a firm's ability to learn, adapt and change their resource configuration in order to produce a series of temporary competitive advantages over time. Lawton and Rajwani (2011, 167) took this line of thinking further and concluded that "dynamic capabilities are the bridge between firm resources and business context" and as such, this concept provided a useful lens through which to examine how media firms adapted their resource base to produce new capabilities and subsequent superior organizational performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We investigate the unique role of senior managers in the exploratory orientation of organizations facing major technological changes and we examine what effect the co-creation of value has in enabling them to perform such roles. This enables us to address the call for further research on the managerial capabilities that underlie effective organizational response to external change (Helfat and Peteraf, 2014) in the specific context of emerging technologies. We also contribute to the discussions on the role of customer co-creation strategies -and customer orientation in general -in company competitiveness and performance.…”
Section: Introductionmentioning
confidence: 99%